A polissemia de "coxinha" no português paulista: uma abordagem segundo a Gramática das Construções Cognitiva - Felippe, Beatriz Daldosso [UNIFESP] (2019)
This dissertation describes and explains the polysemy of the word "coxinha" in Paulista Portuguese, in specific, and in Brazilian Portuguese, in general. Within the framework of Cognitive Linguistics, the approach is formulated according to Cognitive Construction Grammar, a model which emphasizes the development of new meanings out of conventional meanings associated to a grammatical construction. What the dissertation uses from the theory is the conception of meaning as encyclopedic, viewpointed, flexible, and usage-based. What it uses from the model is the conception of polysemy as a radial categorization of meanings motivated by metaphoric and metonymic patterns. Therefore, the word "coxinha" is the grammatical construction that this dissertation takes for its object, which does not include the grammatical constructions of which this is part. Therefore, we address (i) the description of the meanings that the construction shows and (ii) the explanation of its polysemy by means of two cognitive processes: metaphor and metonymy. The pursuit of such aims revealed the insufficiency of the cognitive processes to explain the value of judgement in two new meanings, present in Paulista Portuguese: the one related to the police officer and the one related to a voter profile. In order to explain both of them, we have to appeal to the concept of subjectification, developed by Functional Linguistics and absorbed by Cognitive Linguistics, and we conclude that the subjectification contributes to the systematic polysemy of nouns in the diminutive and participates in the designations we take for metonymic. The construction of the meanings is investigated diachronically: (i) the first meaning of the word "coxinha", entrenched in Brazilian Portuguese, is the name of a snack, and such designation is attributed to metaphor; (ii) the second meaning, new and originated in São Paulo, is a nickname for the civil servant, in general, and the military police officer, in particular, of São Paulo state, and such designation is attributed to metonymy associated with subjectification; and (iii) the third meaning, also new and originated in São Paulo, refers to right-wing voters according to a folk theory of politics, is also attributed to metonymy and subjectification. In this dissertation, metaphor and metonymy remain as cognitive processes responsible for conceptualization, a central phenomenon in Cognitive Linguistics, which defines it as dynamic and imagistic, while subjectification is situated in the realm of viewpoint. Since meaning is defined as viewpointed, encyclopedic, flexible and usage-based,it becomes necessary to distinguish between conceptualization based on cognitive processes and subjectification as a manifestation of viewpoint. Following the usage-based path, we chose the newspaper O Estado de São Paulo as a source of data. Although we do not include usage frequency in our aims, the word was found in several editorials, which led us to divide the tokens of the word in three groups for the formation of a corpus: (i) from 1894 to 1999, for the analysis of "coxinha" as a snack name; (ii) from 2000 to 2012, for the analysis of "coxinha" as the nickname of the police officer; and (iii) from 2013 to 2018, for the analysis of "coxinha" as a voter profile. The division does not imply that the meaning relative to the snack does not occur beyond the first period, or that the meaning relative to the police officer does not occur beyond the second. Our thesis is that perspectivization, a species of which subjectification is a specimen, plays a preponderant role in the development of the latest meanings, given that subjectification is both part of the systematic polysemy relative to the word-formation process and associates with metonymy. Thus, this dissertation contributes to the recognition of the role of metaphor and metonymy with a case study where, without perspectivization, cognitive processes are not enough to explain the value of judgement. By doing so, this dissertation articulates the situated and the distributed characters of cognition, as defended by Cognitive Linguistics and Cognitive Sociolinguistics.